PERAN ORANG TUA DALAM LITERASI ANTIKORUPSI PADA ANAK - AKBAR, SARI AISYAH DZAHABIYAH; SABILA, HIDAYANA; NABILA, MAHARANI; ATIKAH, ZAHRA; HAMIDO, HENDRIKSON (ACADEMIA: Jurnal Inovasi Riset Akademik, 2024)
Corruption is a social problem that impacts various aspects of life, including the education and morality of the younger generation. Instilling anti-corruption values ??from an early age is important to form honest and responsible children's character. According to Izzati & Suyadi (2023), the anti-corruption literacy model describes how anti-corruption is implemented in early childhood. This research aims to analyze the role of parents in anti-corruption literacy in children and how these values ??can be instilled effectively in the family environment. Through a qualitative approach, this research explores parents' perceptions and efforts to introduce the concept of anti-corruption through the habit of honest behavior, good role models and discussions about the importance of integrity. The research results show that parents have a key role in educating children about the negative impacts of corruption by integrating anti-corruption values ??in everyday life. Parents who are actively involved in their children's moral education can help form critical awareness of acts of corruption and develop a strong anti-corruption attitude. This research concludes that anti-corruption literacy in the family is very necessary to prepare children as a generation with integrity and responsibility in the future. ABSTRAKKorupsi merupakan salah satu masalah sosial yang berdampak pada berbagai aspek kehidupan termasuk pendidikan dan moralitas generasi muda. Penanaman nilai-nilai antikorupsi sejak dini menjadi penting untuk membentuk karakter anak yang jujur dan bertanggung jawab. Melalui pendekatan kualitatif penelitian ini menggali persepsi dan upaya orang tua dalam mengenalkan konsep antikorupsi melalui pembiasaan perilaku jujur, teladan yang baik serta diskusi mengenai pentingnya integritas. Hasil penelitian menunjukkan bahwa orang tua memiliki peran kunci dalam mengedukasi anak tentang dampak negatif korupsi dengan mengintegrasikan nilai-nilai anti korupsi dalam kehidupan sehari-hari. Orang tua yang secara aktif terlibat dalam pendidikan moral anak dapat membantu membentuk kesadaran kritis terhadap tindakan korupsi dan mengembangkan sikap antikorupsi yang kuat. Penelitian ini menyimpulkan bahwa literasi anti korupsi dalam keluarga sangat diperlukan untuk mempersiapkan anak sebagai generasi yang berintegritas dan bertanggung jawab di masa depan.